Integrasi Cooperative Learning, Total Physical Response, Dan Media Visual Dalam Pembelajaran Kosakata Bahasa Inggris Siswa Sekolah Dasar - Eva Devi Sofyawati; Pipih Setiawati; Annisa Qurotul Aenun (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Vocabulary mastery is an important aspect of English learning because it supports the development of listening, speaking, reading, and writing skills. However, English vocabulary learning at the elementary school level still faces several challenges, including teacher-centered instruction, limited use of learning media, and insufficient student participation. This community service activity aimed to implement a multimodal learning model integrating Cooperative Learning, Total Physical Response (TPR), and visual media in English vocabulary learning for elementary school students. The activity was conducted at SD Negeri 2 Regol, Garut Regency, involving fifth-grade students. The implementation consisted of four stages: preparation, learning implementation, evaluation, and reflection. The learning activities focused on Parts of the Bodythrough vocabulary presentation using visual media, Listen and Do activities based on TPR, Grab the Picture Game, and simple speaking practice. The observation results showed that the multimodal learning activities supported an active and interactive learning environment. Students demonstrated enthusiasm in participating in movement-based activities, group work, and the use of English vocabulary during the activities. Based on the implementation of the activity, the integration of Cooperative Learning, TPR, and visual media can serve as an alternative approach for contextual English vocabulary learning that is appropriate for elementary school students.